DIY Skateparks as temporary disruptions to neoliberal cities: informal learning through micropolitical making. Issue 6 (2nd November 2021) - Hollett, Ty; Vivoni, Francisco
ABSTRACT: DIY skateparks figure among a widening register of informal urban interventions that confront official plans and visions of cities. They are also powerful learning environments that exemplify efforts by youth and adults alike to disrupt the fixity of neoliberalism in urban spaces. Our focus on the production of DIY skateparks offers complementary and nuanced accounts to literature on making, makerspaces, and maker culture. In this article, we seek alternative spaces of creative activity that can expand perspectives on making beyond narrow foci, like STEM. We argue that a refined focus on the minor gestures of skateboarders – evidenced through the creative potential they see in and subsequent ethic of care they show for one another and for the built environment – offers a way forward toward conceiving of making as a sociopolitical process, particularly within and beyond informal, technology-enhanced learning spaces.